AT&T Inc. : a proposed merger with T-Mobile - Hunt, J. Timothy, (SAGE Knowledge. Cases., 2017)
In an effort to gain market share and technological resources, AT&T and T-Mobile USA agreed to a merger that would create the largest mobile carrier in the country. Concerned about preserving competition in the wireless telecommunications industry, the U.S. Department of Justice has filed a lawsuit to block the transaction. AT&Ts management must now decide how to convince stakeholders that the benefits of a deal far outweigh the risks. Without this merger, AT&T would need to find an alternative way to remain competitive.